2015
DOI: 10.5935/abc.20150005
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Dyslipidemia with Statins and Physical Exercises: Recent Findings of Skeletal Muscle Responses

Abstract: Statin treatment in association with physical exercise practice can substantially reduce cardiovascular mortality risk of dyslipidemic individuals, but this practice is associated with myopathic event exacerbation. This study aimed to present the most recent results of specific literature about the effects of statins and its association with physical exercise on skeletal musculature. Thus, a literature review was performed using PubMed and SciELO databases, through the combination of the keywords “statin” AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
0
17
0
5
Order By: Relevance
“…29,30 Many clinical studies have described muscle adverse effects associated with statin monotherapy or the combination of statins and exercise therapy. [31][32][33][34][35] Our present safety analysis showed that acute exercise might exacerbate statin-induced muscle complaints in patients with statins, whereas moderate physical training prior to statin treatment could counteract statin-induced adverse effects in skeletal muscle. Therefore, when treating dyslipidaemic patients undergoing statin treatment, it was suggested that they should undertake about three days per week of moderate intensity aerobic physical activity combined with resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Many clinical studies have described muscle adverse effects associated with statin monotherapy or the combination of statins and exercise therapy. [31][32][33][34][35] Our present safety analysis showed that acute exercise might exacerbate statin-induced muscle complaints in patients with statins, whereas moderate physical training prior to statin treatment could counteract statin-induced adverse effects in skeletal muscle. Therefore, when treating dyslipidaemic patients undergoing statin treatment, it was suggested that they should undertake about three days per week of moderate intensity aerobic physical activity combined with resistance exercise.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com os dados dos pacientes do estudo, o gênero feminino foi predominante, corroborando com dados da literatura (2). Este fato foi atribuído a uma maior utilização dos serviços de saúde pelas mulheres, prevenindo-se e engajando-se mais em cuidados com a saú-de do que os homens (4,10).…”
Section: Resultsunclassified
“…Do total dos pacientes avaliados, 14% apresentaram alteração dessa enzima, o que diferencia de outros dados onde a maioria dos pacientes (83,3%) que faziam uso regular da sinvastatina, apresentaram alteração da fosfatase alcalina (2). Um estudo realizado com 66 pacientes em uso de estatinas após três meses de uso, não mostrou alteração significativa da fosfatase alcalina e a média de alteração foi de 5% em relação ao valor de referência (13).…”
Section: Resultsunclassified
See 2 more Smart Citations